Validation of a new in vitro Sun Protection Factor method to include a wide range of sunscreen product emulsion types. (27th July 2020) - Pissavini, M.; Tricaud, C.; Wiener, G.; Lauer, A.; Contier, M.; Kolbe, L.; Trullás Cabanas, C.; Boyer, F.; Meredith, E.; de Lapuente, J; Dietrich, E.; Matts, P.J.
Abstract: In 2017, Cosmetics Europe performed a double‐blinded ring test of 24 emulsion‐type sunscreen products, across 3 in vivo test laboratories and 3 in vitro test laboratories, using a new candidate in vitro SPF test method. Based on the results of this work, an article was published showing how data derived from a new lead candidate method conform to new International Standards (ISO) acceptance criteria for alternative SPF test methods (Any alternative method should consider the matrix effect and if required, specify the matrix applicability of the method; Criterion 1a: Systematic differences between methods should be negligible: 95% of all individual results of an alternative method are within the range of ±2× reproducibility standard deviation of the in vivo method, that is overall bias must be below 0.5× reproducibility standard deviation of the in vivo method; Criterion 1b: Measurement uncertainty of an alternative method should be below the measurement uncertainty of the in vivo method. Candidate method predicted values must fall within the full 'funnel' (SPF 6‐50+) limits proposed by Cosmetics Europe (derived from the same minimum test design, that is using the ISO24444 Method to measure at least 24 products across at least 3 laboratories using at least 5 test subjects/laboratory, in a blinded fashion).). Of the 24 sunscreen products tested, the majority of emulsions were of the oil‐in‐water (O/W) type, whereas only one was water‐in‐oil (W/O) and there were no products with a mineral‐only sun filter system. In order to confirm the scope of this method, therefore, a new study was conducted that included 73 W/O (12 mineral + organic, 44 mineral only and 17 organic only) and 3 O/W mineral‐only, emulsion‐type sunscreen products (a total of 76 new sunscreen products). When combined with the previous 24 products (tested in 3 different laboratories), this yielded a new data set comprising a total of 100 emulsion‐type sunscreen products, with SPF values ranging from 6 to 50+ (with a total of 148 data points). These products were tested using the double‐plate in vitro SPF test method and compared with the ISO TC217/WG7 acceptance criteria for alternative SPF test methods. Over 95% of paired in vitro : in vivo SPF values lay within the upper and lower limits of the ISO acceptance criteria funnel, with no bias. This new in vitro SPF test method, therefore, meets the minimum requirements for an alternative SPF test method to ISO24444:2010, for emulsion‐type sunscreen products (which make up the majority of marketed sunscreen products). Abstract : Over 95% of paired in vitro : in vivo SPF values lay with in the upper and lower limits of the ISO acceptance criteria funnel, with no bias. This new in vitro SPF test method, therefore, meets the minimum requirements for an alternative SPF test method to ISO24444:2010, for emulsion‐type sunscreen products. Résumé: En 2017, Cosmetics Europe a réalisé un ring test en double aveugle de 24 produits de protection solaire de type émulsion, dans 3 laboratoires de test in vivo et 3 laboratoires de test in vitro, en utilisant une nouvelle méthode de test SPF in vitro. Sur la base des résultats de ces travaux, un article a été publié montrant comment les données dérivées de cette nouvelle méthode sont conformes aux nouveaux critères d'acceptation des normes internationales (ISO) pour les méthodes de test SPF alternatives. Sur les 24 produits de protection solaire testés, la majorité des émulsions étaient du type huile dans l'eau (H / E), tandis qu'un seul était de l'eau dans l'huile (E / H) et il n'y avait aucun produit contenant uniquement des minéraux. Afin de confirmer cette méthode, une nouvelle étude a donc été menée comprenant 73 produits E/ H (12 produits contenant des filtres minéraux + organiques, 44 produits contenant des filtres minéraux uniquement et 17 produits contenant des filtres organiques uniquement) et 3 produits H / E contenant des filtres minéraux uniquement, tous de type émulsion (donc un un total de 76 nouveaux produits de protection solaire). Combiné aux 24 produits précédents (testés dans 3 laboratoires différents), cela a donné un nouvel ensemble de données comprenant un total de 100 produits de protection solaire de type émulsion, avec des valeurs SPF allant de 6 à 50+ (avec un total de 148 points de données) . Ces produits ont été testés à l'aide de la méthode de test SPF in vitro double approche et comparés aux critères d'acceptation de l'ISO TC217 / WG7 pour les méthodes alternatives du SPF in vivo. Plus de 95% des valeurs de SPF appariées in vitro: in vivo se situent dans les limites supérieure et inférieure de l'entonnoir des critères d'acceptation ISO, sans biais. Cette nouvelle méthode de test SPF in vitro, par conséquent, répond aux exigences minimales d'une méthode de test SPF alternative à ISO24444: 2010, pour les produits de protection solaire de type émulsion (qui constituent la majorité des produits de protection solaire commercialisés).